2019
DOI: 10.1167/19.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences point to two separate processes involved in the resolution of binocular rivalry

Abstract: Although binocular rivalry is different from other perceptually bistable phenomena in requiring interocular conflict, it also shares numerous features with those phenomena. This raises the question of whether, and to what extent, the neural bases of binocular rivalry and other bistable phenomena overlap. Here we examine this question using an individual-differences approach. In a first experiment, observers reported perception during four binocular rivalry tasks that differed in the features and retinal locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Multistable illusions are enormously diverse, involving visibility or audibility, perceptual grouping, visual depth or motion, and many kinds of sensory scenes, from schematic to naturalistic. Average switching rates differ greatly and range over at least two orders of magnitude [19], depending on sensory scene, perceptual grouping [53,112,125], continuous or intermittent presentation [64,72], attentional condition [88], individual observer [16,32,89], and many other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Multistable illusions are enormously diverse, involving visibility or audibility, perceptual grouping, visual depth or motion, and many kinds of sensory scenes, from schematic to naturalistic. Average switching rates differ greatly and range over at least two orders of magnitude [19], depending on sensory scene, perceptual grouping [53,112,125], continuous or intermittent presentation [64,72], attentional condition [88], individual observer [16,32,89], and many other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating which other bistable phenomena are correlated with binocular rivalry in terms of the time course of their perceptual fluctuations can increase scientific understanding of binocular rivalry by identifying common factors that drive the perceptual cycles across multiple paradigms. Previous studies ( Brascamp et al., 2019 ; Cao et al., 2018 ; Sheppard & Pettigrew, 2006 ) have indicated that the rate at which perception switches (and, relatedly, the average duration of individual percepts) is strongly correlated between binocular rivalry and bistable plaid perception ( Figure 1 ), suggesting a shared mechanism underlying both phenomena. The next logical question is as follows: what is this mechanism?…”
Section: Introductionmentioning
confidence: 74%
“…The specifications of this stimulus were identical to those of one of the stimuli (“small grating stimulus”) used in a previous study ( Brascamp et al., 2019 , p. 3). Sinusoidal gratings (spatial frequency of 2.0 c/dva, Michelson contrast 0.5, mean luminance same as background luminance) were presented within an annular aperture (inner radius 0.37 dva, outer radius of 0.85 dva) on two separate monitors viewed through a mirror stereoscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of individual variation in BR temporal parameters was historically a focus of interest (reviewed in Wade & Ngo, 2013; see also Miller et al, 2012) but as mentioned, the trend in BR research prior to our 1998 publication was to divert attention from interindividual differences. The current literature is reporting interesting new findings regarding individual variation in BR dynamics (e.g., Brascamp, Becker, & Hambrick, 2018; Brascamp, Qian, Hambrick, & Becker, 2019; Patel, Stuit, & Blake, 2015) and we continue to contribute to such research (Law, Miller, & Ngo, 2017; Law et al, in preparation). Here again, fluctuations of perspectives in science can be observed 20…”
Section: Slow Br In Bd and The Sticky Switch Model Of Bdmentioning
confidence: 82%